Strategic Pathways to Cloud Migration: Insights from Genesys Cloud Transformations - Vipin Kalra (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Cloud migration represents a transformative shift in contact center operations, yet its success hinges on strategic planning and precise execution. This article synthesizes insights from real-world implementations and empirical research to explore critical factors for successful migration to Genesys Cloud. Key success drivers include robust pre-migration evaluation, architectural strategies, security frameworks, and operational governance. Using case studies and industry data, the study demonstrates how phased migration strategies, strong governance structures, and a focus on compliance enable organizations to achieve optimal outcomes. Emphasizing potential risks and mitigation techniques, this article offers actionable guidance for businesses embarking on digital transformation journeys, providing both theoretical models and practical advice to navigate the complexities of cloud migration.